Systematic review of the genus Ostracodinium (Ciliophora, Entodiniomorphida, Ophryoscolecidae) and notes on the taxonomy of Ostracodinium rugoloricatum Kofoid & MacLennan, 1932 - Cedrola, Franciane; Fregulia, Priscila; Da Silva, Zacarias Rosalina João; Rossi, Mariana Fonseca; Mendes, Saulo Moreira; Dias, Roberto Júnio Pedroso (Zootaxa, 2021)
The family Ophryoscolecidae (Ciliophora, Entodiniomorphida) constitutes a diverse and monophyletic group of symbiotic ciliates of herbivorous mammals. The family includes approximately 200 species, distributed in three subfamilies and sixteen genera. The subfamily Diplodiniinae is the most diverse group in Ophryoscolecidae and comprises the genus Ostracodinium, which includes species with two retractable ciliary zones in the anterior body portion, a broad skeletal plate covering almost all the right surface of the body and a variable number of contractile vacuoles. The genus currently comprises 28 species, classified according to body size and shape, position and shape of the nuclear apparatus, number and position of contractile vacuoles, and number and shape of caudal projections. The present study performs a systematic review of the genus Ostracodinium, based on morphological and molecular data, and provides data about geographic distribution and hosts of each species.